"I am yet to encounter any survey that actually reflects my life": a qualitative study of inclusivity in sexual health research. Issue 1 (December 2016) - Carrotte, Elise; Vella, Alyce; Bowring, Anna; Douglass, Caitlin; Hellard, Margaret; Lim, Megan
Abstract Background Heteronormativity describes a set of norms and assumptions pertaining to heterosexual identities and binary gender. In 2015, we conducted our annualSex, Drugs and Rock'n'Roll study, an online health survey of over 1000 Victorians aged 15–29 years. Feedback from participants suggested that our survey contained heteronormative language. In response to this, we aimed to make inclusive changes to our survey via consultation with young gender and sexually diverse (GSD) people. Methods We conducted two semi-structured focus groups in Melbourne with a total of 16 participants (age range: 21–28 years). Participants were mostly cisgender women, and there were two transgender participants and one non-binary participant. Participants also had a range of sexual identities including lesbian, queer, bisexual, pansexual, and asexual. Focus group discussions were transcribed verbatim and analysed thematically. Results Most participants indicated heteronormativity affects their lives in multiple ways, noting its impacts on access to sexual healthcare, invalidating sexual experiences and miscommunication in forms and surveys. Overall, participants emphasised the need for sexual health research to avoid assumptions about behaviour, to be clear and eliminate question ambiguity and avoiding treating gender as binary. Participants also discussed how theSex, Drugs and Rock'n'Roll survey could address a range of sexual behaviours and experiences, rather than focusing on penetrative sex, which many participants found invalidating. Conclusions Our findings have important implications for future health surveys aimed at general populations. We present recommendations that encourage research to be more inclusive to ensure data collection from GSD participants is respectful and rigorous.